Vehicles of opposition influence or agents of the governing majority? Legislative committees and private members' bills in the Hungarian Országgyűlés and the Israeli Knesset. Issue 3 (3rd July 2019) - Nikolenyi, Csaba; Friedberg, Chen
ABSTRACT: In this article, we assess the role and the strength of the legislative committee system of two legislatures: the Hungarian Országgyűlés and the Israeli Knesset, by looking at the fate of private member bills over the past four legislative cycles (1998–2014 in Hungary and 2006–2019 in Israel). We find that Israeli committees allow opposition PMBs to succeed at a significantly higher rate than Hungarian committees do, even though the formal properties of the two committee systems are very similar: during the examined period, more than one-fifth of the laws that were passed by the Knesset were initiated as opposition sponsored PMB, whereas the corresponding number in the Országgyűlés was only one per cent. The central reason for this unexpected divergence in the success rate of opposition sponsored PMBs, in spite of a favourable institutional setting shared by the committee systems of the two parliaments, may lie in the different degrees of party concentration in the two legislative party systems.